2003
DOI: 10.21273/horttech.13.3.0552
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions and Needs of Volunteers at a University- affiliated Public Garden

Abstract: University-affiliated gardens enhance the teaching, research, and outreach missions of the university. Attracting and retaining volunteers is challenging but important for the success of most public gardens. The objective of this case study was to determine the perceptions and needs of volunteers at a university-affiliated public garden. In a focus group format, participants' responses were analyzed to determine the benefits of volunteering to both the participants and the university. Benefits were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
(7 reference statements)
1
12
0
Order By: Relevance
“…Meyer (2004) stated that more than a quarter of Master Gardeners in the Minnesota program left due to dislike or disappointment with the program, or failure to acquire enough horticulture education. Haynes and Trexler (2003) found that organizations must be cognizant of the quality and scope of training programs to ensure that the training meets volunteers' needs. The perceived quality of training materials and educational activities are key to the organization's success.…”
Section: Discussionmentioning
confidence: 99%
“…Meyer (2004) stated that more than a quarter of Master Gardeners in the Minnesota program left due to dislike or disappointment with the program, or failure to acquire enough horticulture education. Haynes and Trexler (2003) found that organizations must be cognizant of the quality and scope of training programs to ensure that the training meets volunteers' needs. The perceived quality of training materials and educational activities are key to the organization's success.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Hodgkinson and Weitzman () and Hobson et al (), we find that the feeling of belonging appears to facilitate both recruitment and retention. Haynes and Trexler () further reported that feeling connected to others became the major motivation over time. This appears to be true for our participants for whom even menial tasks, such as dishwashing, were fun when done with others or for their community.…”
Section: Discussionmentioning
confidence: 99%
“…Reports show the highest initial motivation for people who volunteer as a MG is to learn horticulture and help others (Rohs and Westerfi eld, 1996;Schrock et al, 2000b). Haynes and Trexler (2003) found public garden volunteer motives shifted over time from mission-related to social benefi ts. A lack of time might be interpreted in this survey as a change in priorities.…”
Section: Extension Education Methodsmentioning
confidence: 99%